Pinning and liquid film instability on colloidal crystal growth - Chin, Kah Mun. (2010)
We demonstrated a pinning model to consistently fabricate domain oriented monolayer colloidal arrays without the interruption of grain disorientation along pre-patterned surface relief boundaries via vertical deposition. With careful engineering of pinning, well controlled linear meniscus contact line offers unidirectional growth of colloidal crystal at [110] direction, giving rise to single domain crystal with only twinnings and vacancies present. This is achieved with good understanding of pinning mechanism and enhanced pinning to prevent wavy contact line induced by fingering instability, which is commonly found in liquid wetting film. A supplementary study of physical and chemistry factors involved in pinning enhancement is presented. It is found that surfactants and colloidal particles play significant roles to enhance edge pinning, increasing distance traveled by receding bulk meniscus (during substrate withdrawal) before liquid depinning or rupturing.